Development of FluidInsight: A PBL-Based Mobile Learning Application for Static Fluids - Riski Yulianto Saputra; Dwi Nanto; Devi Solehat (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2026)
The scarcity of interactive media in static fluid topics often poses difficulties in engaging high school students actively and comprehensively. This study seeks to develop FluidInsight, a Problem-Based Learning (PBL)-based Android application created via the Kodular platform to improve student learning outcomes. The research followed a Research and Development (R&D) design using the 4D model, specifically limited to the Develop stage. Participants included 28 eleventh-grade students involved in a one-group pretest-posttest design. Expert validation yielded an average score of 85.6% (highly feasible), while practicality testing through the User Experience Questionnaire (UEQ) showed high ratings in the stimulation (2.143) and attractiveness (2.036) dimensions. The effectiveness test demonstrated an improvement in learning outcomes with an average N-gain score of 0.55 (moderate). These findings indicate that FluidInsight effectively visualizes abstract concepts and facilitates student-centered learning. Therefore, the integration of PBL into Android-based media serves as an innovative digital transformation strategy for physics instruction.